Beneficiaries’ satisfaction of the Distintivo Soludable Ecuador Project - Angélica Salomé Herrera Molina; Jimena Alexandra Morales Guaraca; Paola Maricela Machado Herrera; Carlos Gafas González; Valeria del Rocío Moya Amaguaya; Jacobo Cambil Martín (Medisur)
Foundation: excessive exposure to the sun can be harmful to health; it increases the risk of sunburn, causes premature aging and skin cancer. Objectives: to determine the beneficiaries’ knowledge and satisfaction with the policies on photoprotection implemented in the National University of Chimborazo Health Sciences Faculty. Methods: a descriptive, cross-sectional study was carried out in 782 participants among students, teachers, administrative and service personnel. The analyzed variables were: organizational leadership, including the application of photoprotection policies and the use of shaded areas, effective communication regarding access to the Soludable policy and recommendations for photoprotection and prevention of skin cancer; as well as the training plan with the inclusion of topics in the micro-curriculum of the nursing and medicine careers subjects. Results: 84% awareness of photoprotection in the university community regarding the adoption of practices and models of conduct, 85.1% use of photoprotection measures, 76.1% promotion of photoprotection measures in the university community, and an increase in shaded areas (88%). This project has allowed students and teachers to transfer knowledge to the practice context in healthcare units, as well as in primary care in the community. Conclusions: the healthy policies implementation in the FCS of UNACH on the application of photoprotection measures and prevention of skin cancer have enabled the awareness of the university community.